Olfactory Entanglements: Syntactic Fragmentation & Scentimentality - Prochaska, Joana Naomi (Journal of Ecohumanism, 2024)
This paper focuses on the entangled relationship of smell, affect, and environmental contamination. I show how olfactory memory mediates the relationship between breathing and the uneven distribution of respiratory risks from polluted air. To do so, I examine Cesar Majoranaâ€™s work â€œThe Syntax of Smell,â€ which is performed in the context of an open laboratory. During the performance, Majorana engages with the audience, creating a scent based on their stories, bringing attention to the connections between their memories, their perception of artificiality, and pollution. This paper is divided into two sections focusing on syntactic fragmentation and scentimentality respectively. In the first section, I illustrate how â€œThe Syntax of Smellâ€ manifests both as the concepts of breathing and olfactory aesthetics. I demonstrate how the performance paradoxically criticises and utilizes bio- and necropolitical forces of smell production. In the second section, I explore the affective qualities of olfactory entanglements by zooming in on the relationship between affective responses and toxicity in relation to Michael Eigenâ€™s concept of toxic nourishment as well as cognitive dissonance. Lastly, building on social psychological research, I show that the performanceâ€™s olfactory memory-triggering qualities might contribute to its effectiveness in increasing awareness of air pollution.